Comparative effects of exergame intervention on cardiorespiratory function in obese and normal-weight adults - Andi Miftah Khaerati Darmawan; Husnul Mubarak; Sylvia Evelyn Aritonang; Nuralam Sam; Melda Warliani; Andi Alfian Zainuddin (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Obesity is a major risk factor for cardiovascular disease and metabolic disorders. Exergaming offers an accessible, interactive alternative to promote physical activity. This study aimed to assess the changes in the 6-minute walk test (6MWT), heart rate recovery (HRR), and maximal oxygen uptake (VO2max) in adults with obesity and normal weight after a six-week exergame intervention. Methods: A quasi-experimental pre-post study involved 29 adults (15 obese, 14 normal BMI) who participated in exergame sessions three times of 40 minutes weekly for six weeks. Inclusion criteria included adults aged 18–45 years with a BMI of 18.5–24.9 kg/m² (normal) or ≥25 kg/m² (obese), normal or corrected vision, and willingness to complete the intervention. Exclusion criteria included individuals with cardiovascular, neurological, or uncontrolled medical conditions, recent surgery or hospitalization, pregnancy, participation in other exercise programs within the previous four weeks, cognitive or sensory impairments, withdrawal from the study, repeated absences, or adverse events such as cybersickness. Outcomes included 6MWT distance, HRR, and VO2max. The paired T-test or Wilcoxon test was used for within-group comparisons, and the independent T-test or Mann-Whitney test for between-group analysis. Results: Significant within-group improvements were observed after the intervention. The 6MWT distance increased by 26.21 m, from 364.48 ± 46.92 m to 390.69 ± 43.17 m (p < 0.001). HRR improved by 11.14 bpm, from 24.41 ± 8.35 bpm to 35.55 ± 8.92 bpm (p = 0.003). VO2max increased by 0.79 mL/kg/min, from 14.91 ± 1.85 to 15.70 ± 1.84 mL/kg/min (p < 0.001). However, between-group differences were not statistically significant for 6MWT (p = 0.397), peak heart rate (p = 0.739), HRR (p = 0.220), and VO2max (p = 0.397), indicating similar improvements in both groups. Conclusion: Six weeks of exergaming significantly improved functional capacity and cardiorespiratory fitness comparably in both obese and normal-weight adults, suggesting it was an inclusive and practical option for community-based physical activity programs.